2020
DOI: 10.3892/mmr.2020.11116
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide mononucleotide attenuates glucocorticoid‑induced osteogenic inhibition by regulating the SIRT1/PGC‑1α signaling pathway

Abstract: long-term and high-dose glucocorticoid treatment is recognized as an important influencing factor for osteoporosis and osteonecrosis. nicotinamide mononucleotide (NMN) is an intermediate of NAD + biosynthesis, and is widely used to replenish the levels of NAD +. However, the potential role of NMN in glucocorticoid-induced osteogenic inhibition remains to be demonstrated. in the present study, the protective effects of NMN on dexamethasone (Dex)-induced osteogenic inhibition, and its underlying mechanisms, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Emerging studies have discussed the functions of different sirtuins in the field of osteogenesis during the last decade. SIRT1 mediated the enhancement of osteogenic differentiation by exogenous antioxidants [76,77]. Upregulation of SIRT3 was found during the antioxidation by melatonin in osteogenesis along with strengthening the activity of SOD2 [78].…”
Section: Discussionmentioning
confidence: 94%
“…Emerging studies have discussed the functions of different sirtuins in the field of osteogenesis during the last decade. SIRT1 mediated the enhancement of osteogenic differentiation by exogenous antioxidants [76,77]. Upregulation of SIRT3 was found during the antioxidation by melatonin in osteogenesis along with strengthening the activity of SOD2 [78].…”
Section: Discussionmentioning
confidence: 94%
“…Ascorbic acid may promote the synthesis of collagen I in cultured cells, and regulate ATP and ALP activity and the synthesis of non-collagen matrix proteins ( 37 ). β-glycerophosphate has been shown to provide phosphate ions to osteoblasts, and promote the deposition and calcification of physiological calcium salts, which is a necessary condition for mineralized nodules in BMSCs ( 38 ). When medium contains these components, BMSCs undergo a series of changes, resulting in them obtaining the morphology and growth characteristics of osteoblasts ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…NR can also be used as a precursor for NMN by NR kinase (NRK) in the salvage pathway [ 52 ]. A few studies have revealed that PGC-1α is closely linked to the NAD + salvage pathway ( Figure 1 ), and metabolites in the NAD + salvage pathway, such as NR and NMN, have been shown to upregulate the SIRT1–PGC-1α pathway in the liver [ 36 ] and bone [ 53 ]. Moreover, NAMPT is a rate-limiting enzyme responsible for the conversion of NAD + in the salvage pathway [ 54 , 55 ] and is associated with PGC-1α to generate NAD + in the renal epithelium [ 18 ] and regulates mitochondrial biogenesis via NAD metabolism in the skeletal muscle [ 56 ].…”
Section: Nad + Biosynthesismentioning
confidence: 99%
“…However, further studies are required to understand the relationship between NAMPTs and PGC-1α in the NAD + salvage pathway in various tissues. NMN treatment has also been shown to alleviate osteogenic inhibition and promote the expression of SIRT1 and PGC-1α, whereas these beneficial effects of NMN were reversed when SIRT1 and PGC-1α were decreased [ 53 ]. Thus, the SIRT1–PGC-1α pathway may be involved in the conversion of NMN into NAD + ; however, the mechanism by which SIRT1–PGC-1α regulates NMNAT to convert NMN into NAD + is still poorly understood.…”
Section: Nad + Biosynthesismentioning
confidence: 99%
See 1 more Smart Citation